Tipe Kurikulum dan Implementasinya terhadap Manajemen Sekolah di MINU KH Mukmin Sidoarjo - Arinil, Zanneta; Iffat, Chanifatul; Batrisyiah, Filzah; Gading, Waming; Amalia, Kaniati (Lembaga Yasin AlSys, 2024)
Non-formal education is present as an effort in a more special learning process, namely increasing the potential of students who are more special. Madrasah Ibtidaiyah Nahdhatul Ulama KH Mukmin is a non-formal educational institution based on aswaja. In the ibtidaiyah madrasah, it is tentative to develop a curriculum for the institution in the future. The purpose of writing this article is to find out what type of curriculum is used in this Madrasah and find out how the implications of using the curriculum used on school management in this Madrasah Ibtidaiyah. The research method of this article uses a qualitative approach which conducts data collection directly through interviews. The results show that this school uses the Merdeka curriculum with a curriculum development process using planning, organizing, actuating, and controlling stages. The implications of using the Merdeka curriculum in madrasah are more effectively used and learning becomes more detailed. The independent curriculum emphasizes project-based learning, focuses on important material, and is more flexible in learning. The independent curriculum also provides opportunities for students to develop their talents and skills, especially in the field of technology.